THE EFFECT OF CREDIT ASSESSMENT AND HUMAN RESOURCE QUALITY ON THE DECISION TO PROVIDE BUSINESS DEVELOPMENT CAPITAL - Wahyuni, Sri Fitri; Hafiz, Muhammad Shareza; Pradesyah, Riyan (Proceeding International Seminar of Islamic Studies, 2022)
Credit is a provision of loans to the community, in order for an activity that is consumptive and productive. Usually, credit is given by financial institutions such as banks, where banks will provide credit to people who have met the conditions set by the bank. In this case, productive credit is given to people who want to open a business or develop a business that is already owned. But most of the requirements given by banks or financial institutions are not in accordance with reality, where the bank also assesses the human resources that exist in the business being run. This research, is a quantitative study, with analytical tools using SPSS. As for the results obtained, that there is a partial influence of credit assessment on the decision to provide business development capital. The quality of human resources partially affects the provision of business development capital. And simultaneously, the credit assessment and quality of human resources affect the provision of business development capital, with a value of Rsequer 53.2%